Personal financial planning using rule based expert system - Cheah, Jit Choon (2014)
Personal Financial Planning Application is a web-based application that implemented by artificial intelligence technique. The idea behind this project development is the statistic shows that there is an amount of number of Malaysian young group people in declared as bankruptcy. Most of the problem is that people cannot manage their finances in a proper way. This application developed to help people manage and control their expenses by giving suggestions base on their monthly salary. By using Rule Based Expert Application technique, this application has generated a suggestion on personal financial by month regarding the expenses. Based on this application, the priority must be clear all the debt and having some saving. This application already scoped into a fresh graduate student that had been started work in real life. By key in monthly income status, this application will be produced and gave a suggestion for personal financial planning. This application completely developed by guideline for Rapid Application Development (RAD) software process that very effective to finish this development process.